Proton irradiation-decelerated intergranular corrosion of Ni-Cr alloys in molten salt - Weiyue Zhou; Yang Yang; Guiqiu Zheng; Kevin B. Woller; Peter W. Stahle; Andrew M. Minor; Michael P. Short (Nature Communications, 2020)
Abstract The effects of ionizing radiation on materials often reduce to “bad news”. Radiation damage usually leads to detrimental effects such as embrittlement, accelerated creep, phase instability, and radiation-altered corrosion. Here we report that proton irradiation decelerates intergranular corrosion of Ni-Cr alloys in molten fluoride salt at 650 °C. We demonstrate this by showing that the depth of intergranular voids resulting from Cr leaching into the salt is reduced by proton irradiation alone. Interstitial defects generated from irradiation enhance diffusion, more rapidly replenishing corrosion-injected vacancies with alloy constituents, thus playing the crucial role in decelerating corrosion. Our results show that irradiation can have a positive impact on materials performance, challenging our view that radiation damage usually results in negative effects.